TEACHING LITERACY THROUGH PLAY: INDONESIAN EARLY CHILDHOOD TEACHERS PRESPECTIVE - Wili Astuti (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2021)
In Early childhood education, play is considered as the heart of instruction and learning prepare. Play moreover critical in obtaining children language and literacy ability, person with higher level of proficiency have higher opportunity in their life success. This is a qualitative research study analysing teacher's conceptualization of play in the literacy teaching and learning process. An interpretative and descriptive qualitative research is the design of this study. A qualitative study was undertaken because this technique allows researchers with ways and means considering different views of the research subject therefore producing rich, in-depth and elaborate data. This, small research has been conducted in Indonesian settings on the utilize of play in educating proficiency in early childhood instruction classrooms. Information was obtained through one-on-one, one-hour in-depth interviews from a few teachers in five early childhood education institutions. Examination of the information uncovered those early education teachers agree on utilizing play as an instrument in educating literacy concepts